2020
DOI: 10.1002/jcp.29926
|View full text |Cite
|
Sign up to set email alerts
|

Enolase‐phosphatase 1 acts as an oncogenic driver in glioma

Abstract: Enolase-phosphatase 1 (ENOPH1), a newly identified enzyme involved in L-methionine biosynthesis, is associated with anxiety and depression. In this study, ENOPH1 was found to play a crucial role in promoting the proliferation and migration of glioma cells. Among high-grade glioma patients, the overall survival of the group showing high ENOPH1 expression was shorter than that of the group showing low ENOPH1 expression. ENOPH1 knockdown inhibited glioma cell proliferation and migration. In parallel, ENOPH1 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Methionine metabolism is critical for white matter synthesis and is defective in human AD (Linnebank et al, 2010;Hooshmand et al, 2019;Mihara et al, 2022) and in the CVN-AD mouse (Colton, CA, unpublished observations). Enolase-phosphatase 1 (Enoph1), which is highly expressed in stress responses of the brain (Wang et al, 2005;Fagerberg et al, 2014), is also involved in methionine salvage (Pirkov et al, 2008;Barth et al, 2014;Wang et al, 2021). Down regulation of this enzyme in this mouse model further implicates methionine disruption as a likely contributor to AD-like brain pathology.…”
Section: Lasso Regressionmentioning
confidence: 90%
“…Methionine metabolism is critical for white matter synthesis and is defective in human AD (Linnebank et al, 2010;Hooshmand et al, 2019;Mihara et al, 2022) and in the CVN-AD mouse (Colton, CA, unpublished observations). Enolase-phosphatase 1 (Enoph1), which is highly expressed in stress responses of the brain (Wang et al, 2005;Fagerberg et al, 2014), is also involved in methionine salvage (Pirkov et al, 2008;Barth et al, 2014;Wang et al, 2021). Down regulation of this enzyme in this mouse model further implicates methionine disruption as a likely contributor to AD-like brain pathology.…”
Section: Lasso Regressionmentioning
confidence: 90%
“…A vivo research demonstrated that asparagine depletion could obviously inhibit the tumor growth of KRAS-mutant CRC cells (Hanada et al, 2021). Enolase-phosphatase 1 (ENOPH1), whose protein is an enzyme that participates in L-methionine Frontiers in Molecular Biosciences frontiersin.org biosynthesis, has been discovered to enhance the progression and invasion of glioma and hepatocellular carcinoma but has not been reported in colorectal cancer (Zhuang et al, 2019;Wang et al, 2021). The function of ACAT1, ALDH4A1, and FAS in colorectal cancer has been verified by previous studies, participating in the progression of CRC.…”
Section: Discussionmentioning
confidence: 99%